2006
DOI: 10.1080/13693780600794533
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in coccidioidomycosis. Quantification and correlation with clinical, immunological, and nutritional factors

Abstract: While described in the past, the frequency and degree of fatigue associated with symptomatic coccidioidomycosis has never been quantified. Using the Fatigue Severity Scale (FSS), severe fatigue (FSS score = 41) was found in 65% of cases of active coccidioidomycosis compared to 42% in cohort of control subjects with chronic medical diseases (P=0.024). Fatigue in patients with symptomatic coccidioidomycosis declined significantly over four months (P=0.023). Severe fatigue in patients with symptomatic coccidioido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Other investigators have demonstrated a median time of 95–98 days (roughly 14 weeks) to 50% resolution of symptoms ( 11 ). Still others have found that fatigue is severe at baseline and 4 months later ( 10 ) and that >25% of otherwise healthy college students with primary coccidioidomycosis required medical care for at least 4 months ( 22 ). Although our study focused only on persons with mild to moderate infection and no substantial concurrent conditions, results are similar to those of previous studies (long duration of symptoms, fatigue, and illness caused by primary coccidioidal infection).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have demonstrated a median time of 95–98 days (roughly 14 weeks) to 50% resolution of symptoms ( 11 ). Still others have found that fatigue is severe at baseline and 4 months later ( 10 ) and that >25% of otherwise healthy college students with primary coccidioidomycosis required medical care for at least 4 months ( 22 ). Although our study focused only on persons with mild to moderate infection and no substantial concurrent conditions, results are similar to those of previous studies (long duration of symptoms, fatigue, and illness caused by primary coccidioidal infection).…”
Section: Discussionmentioning
confidence: 99%
“…When this score declined to 50% of the enrollment score for 2 consecutive weeks, symptoms were assessed every 2 weeks for 2 episodes, then monthly for 6-month follow-up visits. Baseline and monthly fatigue levels were assessed by using the fatigue severity scale ( 10 , 18 ), and health-related quality of life was assessed by using the 36-Item Short Form Health Survey ( 19 ). Full-time or part-time attendance at work or school was recorded during assessments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptoms are cough, fever, headache, and chest pain, each occurring in more than 70% of patients (23). Helpful clinical symptoms are night sweats and prolonged fatigue, which may take months to resolve (2,37). Approximately 25% of white women and 4% of white men develop "valley fever," an allergic syndrome characterized by hypersensitive skin lesions, such as erythema multiforme or erythema nodosum, and polyserositis (10).…”
Section: Acute Diseasementioning
confidence: 99%
“…Previous studies addressing fatigue in this population have been limited to subjective reports [3, 4]. In this report, we conducted physiologic measurements (ie, strength, pulmonary function, exercise capacity, gas exchange) in 5 individuals with self-reported fatigue after coccidioidal pneumonia without evidence of hematogenous dissemination.…”
mentioning
confidence: 99%